2018
DOI: 10.22515/jifa.v1i1.1135
|View full text |Cite
|
Sign up to set email alerts
|

Tax Minimization sebagai Pemoderasi Hubungan antara Tunneling Incentive, Bonus Mechanism dan Debt Convenant dengan Keputusan Transfer Pricing

Abstract: This research is purposed to determine the effect of tunneling incentive,bonus mechanism and debt covenant to transfer pricing wich ismoderated by tax minimization on multinational firm’s listed atIndonesian Stock Exchange in 2012-2014. The technique of thisanalysis is multiple regression analysis, wich used 33 annual reportfrom secondary data with purposive sampling method. The result ofthis research showed that variabel which are having a significantimpact to transfer pricing are tunneling incentive, debt co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
34

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 0 publications
1
14
0
34
Order By: Relevance
“…Research by Tang (2016) indicates that tunneling incentives have a substantial positive impact on tax avoidance. Besides, research from Azzura & Pratama (2019) and Nuradila & Wibowo (2018) has shown that tunneling incentives have a major impact on Indonesia's transfer pricing. While the business becomes a public enterprise, the group's influence is still significant (Susanti & Firmansyah, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Tang (2016) indicates that tunneling incentives have a substantial positive impact on tax avoidance. Besides, research from Azzura & Pratama (2019) and Nuradila & Wibowo (2018) has shown that tunneling incentives have a major impact on Indonesia's transfer pricing. While the business becomes a public enterprise, the group's influence is still significant (Susanti & Firmansyah, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Merle et al (2019) from France found that increasing leverage using DER would affect higher transfer pricing. Nuradila & Wibowo (2018) research has found a positive and significant influence of the debt covenant on rising transfer pricing. Companies tend to pay lenders' interest.…”
Section: H3mentioning
confidence: 99%
“…Mengacu pada penelitian Mutamimah (2008) dan Nuradila & Wibowo (2018), tunneling incentive pada penelitian ini diukur dengan rumus sebagai berikut:…”
Section: Harga Transferunclassified
“…Tax minimization merupakan strategi yang dilakukan perusahaan untuk meminimalkan tanggungan beban pajak perusahaan. (Nuradila & Wibowo, 2018) menemukan bahwa motivasi dilakukannya harga transfer dengan cara merekayasan pembebanan harga transaksi antar perusahaan terafiliasi dengan maksud untuk meminimalkan tanggungan jumlah pajak secara keseluruhan. Praktik harga transfer dipicu dengan adanya beban pajak yang tinggi yang harus ditanggung perusahaan, hal tersebut dilakukan dengan tujuan untuk menekan beban yang ditanggung (Mayantya, 2018).…”
Section: Tax Minimization Dapat Memperkuat Pengaruh Positif Dalam Hubunclassified
“…Prestasi kerja dapat diukur berdasarkan penilaian secara objektif perusahaan dengan melihat laba yang dihasilkan (Nurmanto, 2017). Mekanisme bonus yaitu skema perusahaan dalam mengoptimalkan penerimaan bonus oleh direksi dengan melakukan peningkatan profit perusahaan secara menyeluruhan (Nuradila & Wibowo, 2018). Variabel Mekanisme Bonus diukur dengan Indeks Trend Laba Bersih (ITRENDLB) yang didasarkan kepada penerimaan lababersih tahun t terhadap laba bersih tahun t-1.…”
Section: Mekanisme Bonus (X2)unclassified